Ellissi, catastrofi, quanti. Forme del Neobarocco tra estetica e pensiero scientifico - Montefameglio, Alessandro (Aesthetica Preprint, 2023)
This article examines specific aesthetic and philosophical aspects of the Neobaroque category, with particular emphasis on its development in the late 20th century. In this sense, Neobaroque is conceived as a category that does not designate the repetition of the characteristics of historical Baroque, but that instead identifies an underlying logic of form in contemporary aesthetic phenomena. Specifically, we focus on the paradigms presented by Severo Sarduy and Omar Calabrese, with special attention to the interplay between aesthetics and science in their works. After an introductive paragraph (1), providing a brief overview of the essential historical and philosophical coordinates of Neobaroque, we analyse (2) Sarduy’s concept of retombée and its implications. Moving to Calabrese’s paradigm (3), we examine how the semiotician conceptually and methodologically expands the architecture of the previous model, establishing it as an authentic logic of form. The last paragraph (4) briefly explores the potential application and adaptability of the Neobaroque category in contemporary times.